Communication barriers in learning during pandemic and its pedagogical approaches - Maria Aurora G. Victoriano; Lodecy V. Ocbeña (Institute of Advanced Engineering and Science, 2024)
Communication is an essential element of life. It is crucial when it comes to education which is a tool for the welfare of society. People socialize via communication and thus perform desired behaviors. Because of these reasons, preventing communication barriers will provide a more specific field of experience between the sender and the receiver. The study sought to determine the communication barriers among students of Capiz State University, Mambusao Satellite College, Philippines, learning during the pandemic. The study used descriptive and qualitative methods. An in-depth interview using a semi-structured questionnaire was the researcher’s data-gathering instrument. Eight students were the study participants chosen based on the criteria. The study shows that communication between students and teachers has shifted to the digital realm using cell phones and social media. The primary focus of these conversations is module-related matters, and the students initiate the conversation due to module-related problems. Different pedagogical approaches highlight the need to improve communication and effective teaching and learning in the new normal. Despite the pandemic, it is recommended that students and teachers continue to communicate and collaborate. Teachers must also promote creativity in their classes and conduct intervention activities to help students overcome communication barriers.